Importance of high triglycerides levels between novel coronary risk factors (2017)
Introduction: The analysis of new cardiovascular risk factors is under an extensive debate in the cardiology and metabolic research fields. Objective: To determine the main factors that contribute to the classification of individuals with higher coronary risk in the adult population from Maracaibo, Venezuela. Methods: A descriptive, cross-sectional study with multistage random sampling in 1379 individuals belonging to the Maracaibo City Metabolic Syndrome Prevalence Study (MMSPS) was performed. They were classified according to the coronary risk by Framingham-Wilson equation adapted to our population. The association between various risk factors was evaluated by ordinal logistic regression models. Results: 1,379 subjects (females 55.9%; n = 771) were evaluated, 66.2% (n = 913) were classified with low coronary risk. In univariate ( 2 = 112.35; p < 0.00001) and multivariate analysis [OR: 3.98 (2.39-6.63); p < 0.01], the main factors associated to be classified as the highest risk category were hypertriglyceridemia. Conclusion: There are several factors that should be included in predictive models use worldwide. The most important in our population were dyslipidemia such as hypertriglyceridemia, hyperlipoproteinemia (a) and insulin resistance.